Waterpipe Tobacco and Cigarette Smoking Direct Comparison of Toxicant Exposure - Eissenberg, Thomas (2009)
BACKGROUND: Waterpipe (hookah, shisha) tobacco smoking has spread worldwide. Many waterpipe smokers believe that, relative to cigarettes, waterpipes are associated with lower smoke toxicant levels and fewer health risks. For physicians to address these beliefs credibly, waterpipe and cigarette must be compared directly. PURPOSE: The purpose of this study is to provide the first controlled, direct laboratory comparison of the toxicant exposure associated with waterpipe tobacco and cigarette smoking METHODS: Participants (N=31; mean=21.4 years, SD=2.3) reporting monthly waterpipe use (mean 5.2 uses/month, SD=4.0) and weekly cigarette smoking (mean= 9.9 cigarettes/day, SD=6.4) completed a crossover study in which they each smoked a waterpipe for a maximum of 45 minutes or a single cigarette. Outcomes included expired air carbon monoxide (CO) 5 minutes after session’s end, and blood carboxyhemoglobin (COHb), plasma nicotine, heart rate, and puff topography. Data were collected in 2008–2009 and analyzed in 2009. RESULTS: CO increased, on average, by 23.9 ppm for waterpipe (SD=19.8) and 2.7 ppm for cigarette (SD=1.8) while peak waterpipe COHb levels (mean=3.9%, SD=2.5) were three times those observed for the cigarette (mean=1.3%, SD=0.5; Ps<0.001). Peak nicotine levels did not differ (mean ng/ml waterpipe=10.2, SD=7.0; cigarette=10.6, SD=7.7). Significant heart rate increases relative to pre-smoking were observed 5, 10, 15, 20, 25, and 35 minutes during the cigarette session and at every 5-minute interval during the waterpipe session (Ps<0.001). Mean total puff volume was 48.6 liters for waterpipe as compared to 1.0 liters for cigarette (P<0.001). CONCLUSIONS: Relative to a cigarette, waterpipe use is associated with greater CO, similar nicotine, and dramatically more smoke exposure. Physicians should consider advising their patients that waterpipe tobacco smoking exposes them to some of the same toxicants as cigarette smoking and therefore the two tobacco smoking methods likely share some of the same health risks.